How best practices are copied, transferred, or translated between health care facilities: A conceptual framework. Issue 3 (July 2015) - Guzman, Gustavo; Fitzgerald, Janna Anneke; Fulop, Liz; Hayes, Kathryn; Poropat, Arthur; Avery, Mark; Campbell, Steve; Fisher, Ron; Gapp, Rod; Herington, Carmel; McPhail, Ruth; Vecchio, Nerina
Abstract : Introduction: In spite of significant investment in quality programs and activities, there is a persistent struggle to achieve quality outcomes and performance improvements within the constraints and support of sociopolitical parsimonies. Equally, such constraints have intensified the need to better understand the best practice methods for achieving quality improvements in health care organizations over time. This study proposes a conceptual framework to assist with strategies for the copying, transferring, and/or translation of best practice between different health care facilities. Purpose: Applying a deductive logic, the conceptual framework was developed by blending selected theoretical lenses drawn from the knowledge management and organizational learning literatures. Findings: The proposed framework highlighted that (a) major constraints need to be addressed to turn best practices into everyday practices and (b) double-loop learning is an adequate learning mode to copy and to transfer best practices and deuteron learning mode is a more suitable learning mode for translating best practice. We also found that, in complex organizations, copying, transferring, and translating new knowledge is more difficult than in smaller, less complex organizations. We also posit that knowledge translation cannot happen without transfer and copy, and transfer cannot happen without copy of best practices. Hence, an integration of all three learning processes is required for knowledge translation (copy best practice–transfer knowledge about best practice–translation of best practice into new context). In addition, the higher the level of complexity of the organization, the more best practice is tacit oriented and, in this case, the higher the level of K&L capabilities are required to successfully copy, transfer, and/or translate best practices between organizations. Practice Implications: The approach provides a framework for assessing organizational context and capabilities to guide copy/transfer/translation of best practices. A roadmap is provided to assist managers and practitioners to select appropriate learning modes for building success and positive systemic change.